Monitoring Marine Areas from the International Space Station: The Case of the Submerged Harbor of Amathus - Cerra, Daniele; Gege, Peter; Evagorou, Evagoras S.; Agapiou, Athos; De los Reyes, Raquel (My University, 2021)
The submerged harbor of Amathus in Cyprus is a sensitive cultural heritage requiring special attention in the frame of Marine Spatial Planning. The monitoring of water depth in the surrounding area can raise awareness on effects, such as shoreline erosion, which could lead to a deterioration of the relics. This paper assesses the quality of bathymetric maps around the site derived from the DESIS hyperspectral sensor mounted on the International Space Station. The depth values are compared to products derived from traditional multispectral sensors, and assessed with LiDAR measurements acquired in situ. An imaging spectrometer such as DESIS would be able to derive additional water quality parameter such as phytoplankton concentration, assessing at the same time eutrophication and pollution in this sensitive area.
Keywords: Amathus; Bathymetry; Cultural heritage; Cyprus; DESIS; Imaging spectrometry; Marine spatial planning; Remote sensing